2018
DOI: 10.1186/s12862-018-1136-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of CYP2J19, a gene involved in colour vision and red coloration in birds: positive selection in the face of conservation and pleiotropy

Abstract: BackgroundExaggerated signals, such as brilliant colours, are usually assumed to evolve through antagonistic coevolution between senders and receivers, but the underlying genetic mechanisms are rarely known. Here we explore a recently identified “redness gene”, CYP2J19, that is highly interesting in this context since it encodes a carotenoid-modifying enzyme (a C4 ketolase involved in both colour signalling and colour discrimination in the red (long wavelength) spectral region.)ResultsA single full-length CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
(52 reference statements)
3
23
0
Order By: Relevance
“…Our results corroborate a growing number of studies suggesting the importance of CYP2J19 for red coloration in birds [23,24,82,83] and other animals [84,85]. The genetic basis of carotenoid-based coloration is not yet well resolved [3,32], but a handful of genes with large effects have been identified in recent years that are associated with carotenoid coloration (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Our results corroborate a growing number of studies suggesting the importance of CYP2J19 for red coloration in birds [23,24,82,83] and other animals [84,85]. The genetic basis of carotenoid-based coloration is not yet well resolved [3,32], but a handful of genes with large effects have been identified in recent years that are associated with carotenoid coloration (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…It therefore appears that the estrildid CYP2J19 duplication occurred after the split between ploceids and estrildids. More broadly, a single copy of CYP2J19 was reported also in the red factor canary (Lopes et al., ), as well as in chicken and ostrich (Twyman et al., ) and GenBank searches reveal only a single copy in the vast majority of available avian genomes (Emerling, , Twyman, Andersson, & Mundy, ), which means that a single CYP2J19 copy probably is the “normal” situation for birds.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two molecular studies in coloration of two mutant bird systems: the yellowbeak in zebra finch mutant (Mundy et al 2016) and the red factor in canary (Lopes et al 2016) have identified a gene, Cyp2j19, as a ketolase responsible for the conversion of yellow dietary carotenoids into red ketocarotenoids. A single copy of Cyp2j19 appears to be widespread across avian lineages (Twyman et al 2018).…”
Section: Introductionmentioning
confidence: 99%